Potential profound fluctuation in tacrolimus concentration on consumption of pomegranate rind extract: A Pharmacokinetic Experiment - Karwasra, Ritu; Ahmad, Sayeed; Singh, Surender (Frontiers in Pharmacology, 2023)
Background: Presently, varied case reports demonstrated an increase or decrease in blood concentration of diverse conventional drugs, often co-administered with edible fruits, spices, or vegetables. The overarching aim of this research is to elucidate the fluctuations in tacrolimus (TAC) blood concentration on the consumption of pomegranate rind extract (PRE). Methods: Pharmacokinetic (PK) study was conducted with two groups, viz-a-viz PRE+ TAC (3mg/kg) and TAC (3mg/kg) alone group. Experimental study was conducted in three different manners; Single-dose (S) PRE (200 mg/kg), seven-day repetitive (7-R) PRE (200 mg/kg) dosing, multiple (M) PRE doses (100, 200, 400 and 800 mg/kg). All the blood samples (approximately 300 μl) were withdrawn at diverse time intervals i.e. 30 min, 1 hr, 2hr, 4hr, 8hr, and 12hr after oral administration of TAC (3 mg/kg). Estimation of TAC in rat plasma was done by using the hyphenated technique LC-MS/MS where the mass spectrometer used was triple-stage quadruple and using multiple reactions monitoring (MRM) mode. Results: Findings depict that on comparison with TAC (3mg/kg) alone group in the seven-day repetitive (7-R) PRE dose study, the Cmax was found to be 9.03±1.21 ng/ml; AUC from time zero to infinity (AUC0-∞), 61.91±17.37 ngh/ml, whilst TAC (3mg/kg)+ PRE group exhibited an increase in PK parameters of TAC (Cmax 22.48±3.07 ng/ml; AUC0-∞ 153.08±13.24 ng h/ml). The authors further investigated in what manner the PRE affects the PK of TAC in animals. For this, docking studies with major phytoconstituents present in PRE with CYP3A4 isoenzyme were carried out. Ellagitannins (dock score -11.64) and punicalagin (dock score -10.68) were again used for molecular simulation studies with TAC. To validate our findings, a CYP3A4 inhibitory in-vitro assay was conducted. Conclusion: Based on integrated in-vivo and in-silico studies, we concluded that pomegranate rind extract interacts strongly with CYP isoenzyme, and is therefore responsible for the altered PK profile of TAC.